[18F]PBR146 and [18F]DPA-714 in vivo Imaging of Neuroinflammation in Chronic Hepatic Encephalopathy Rats - Kong, Xiang; Luo, Song; Wang, Yun Fei; Yang, Gui Fen; Lu, Guang Ming; Zhang, Long Jiang (Frontiers in Neuroscience, 2021)
Neuroinflammation is an important pathogenesis of hepatic encephalopathy (HE). The upregulation of translocator protein (TSPO) during neuroinflammation provides an imaging molecular target to evaluate the severity of neuroinflammation in chronic HE rats. [18F]DPA-714 and [18F]PBR146 targeting TSPO are often used for neuroinflammation imaging. This study performed bile duct ligation (BDL) in rats to simulate chronic HE model, tested the behavioral experiments, and conducted [18F]PBR146 and [18F]DPA-714 micro-PET/CT scans followed analyzing the average %ID/g values of the whole brain, brain regions and main organs of subjects. After sacrifice the rats, the blood plasma samples were taken for blood biochemical indexes and plasma inflammatory factor levels examination, the liver and brain specimens were obtained for pathological analysis. The BDL rats showed chronic liver failure with defects in cognition, motor coordination ability and mental state. [18F]PBR146 and [18F]DPA-714 micro-PET/CT imaging results were similar in whole brain of BDL group and Sham group. Besides, some regional brain areas in BDL rats were found abnormal uptakes mainly located in basal ganglia area, auditory cortex, motor cortex, cingulate gyrus, somatosensory cortex, hippocampus, thalamus, midbrain and medulla oblongata, and these regions also correlated with behavioral alterations. In conclusion, both [18F]PBR146 and [18F]DPA-714 had the similar imaging effects in hepatic encephalopathy models could quantitatively evaluate neuroinflammation load and distribution. The difference brain regions with higher uptake values of radiotracers in BDL rats were correlated with behavioral alterations.